2019
DOI: 10.1002/psc.3140
|View full text |Cite
|
Sign up to set email alerts
|

Improved synthesis on solid phase of dithiocarbamic cRGD‐derivative and 99mTc‐radiolabelling

Abstract: In the field of angiogenesis, small cyclic pentapeptides containing the RGD motif are playing a relevant role for their high affinity and specificity for integrin receptors and for the possibility to act at both therapeutic and diagnostic level by inhibiting pathological angiogenesis and by serving as shuttles to deliver imaging-probe including SPECT/PET radionuclides to specific tissues.In the last decade, several new protocols were reported in literature for the direct synthesis of cyclic RDG either in solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We found that the non-functionalized PEG microbeads were more compatible with various solvents due to the increase in amphiphilicity [22]. Compared with commercially available PEG-based microbeads, such as PEGA resin [23,24], TentaGel XV resin [25,26], and ChemMatrix resin [27,28], PEG-amine hydrogel microbeads did not swell relatively with various solvents because of the high degree of crosslink [4,5]. However, our PEG-amine microbeads did not need a high swelling ratio because most of the active functional groups were exposed at the shell region [22,29].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the non-functionalized PEG microbeads were more compatible with various solvents due to the increase in amphiphilicity [22]. Compared with commercially available PEG-based microbeads, such as PEGA resin [23,24], TentaGel XV resin [25,26], and ChemMatrix resin [27,28], PEG-amine hydrogel microbeads did not swell relatively with various solvents because of the high degree of crosslink [4,5]. However, our PEG-amine microbeads did not need a high swelling ratio because most of the active functional groups were exposed at the shell region [22,29].…”
Section: Resultsmentioning
confidence: 99%
“…They are highly correlated with angiogenesis, tumorigenesis, metastasis, and drug resistance [84][85][86]. In particular, integrin α v β 3 isoform represents an interesting molecular target for many diagnostic and therapeutic applications [87][88][89][90]. α v β 3 specifically recognizes the consensus tripeptide Arg-Gly-Asp (RGD), derived from extracellular matrix proteins, which has been largely exploited as radiolabeled carrier for the early diagnosis of malignant tumors [91].…”
Section: Anticancer Applications-diagnosticmentioning
confidence: 99%
“…Besides, [ 99m Tc][TcN(S 2 CNR 2 ) 2 ] complexes containing the 4-(cyclohexylpiperazine) scaffold were used for the imaging of sigma receptors overexpressed in a variety of cancers [124]; likewise, the 2-methoxyphenylpiperazine moiety was tested for 5-HT1A receptor binding for imaging of brain disorders [125] and the RGDfK motif for non-invasive imaging of α v β 3 expression in malignant tumors [126,127].…”
Section: Labeling Of Biologically Active Molecules: Target Specific Cmentioning
confidence: 99%